Reactive hydrocarbons (C6-C11) in the Metropolitan Area of São Paulo - Coelho, Monique Silva (2023)
Volatile organic compounds (VOCs) are fundamental in the atmospheric reactions, producing tropospheric ozone (O3) and secondary organic aerosols (SOA). Among the VOCs, hydrocarbons (HCs) stand out, including the aromatics compounds (e.g., BTEX: benzene, toluene, ethylbenzene, m,p- and o-xylenes) being emitted directly into the atmosphere, in urban areas, by vehicle exhausts, fuel evaporation, solvent use, emissions of natural gas, and industrial processes. São Paulo is the Brazilian state with the largest territorial occupation and more than 47 million inhabitants, added to the greater economic development and the largest automotive fleet, causing degradation of air quality. At metropolitan area of São Paulo (MASP) the vehicle fleet of more than 7 million vehicles has been recognized as the main cause of air pollution events. But health problems and complaints from the population around an important industrial and petrochemical complex at MASP have also received special attention. In this context, the present study evaluated the HCs close to the Capuava Petrochemical Complex (CPC) in MASP, from 2016 to 2022. In the first step were analyzed data of different HCs based hourly sampling in two different sites during different days, 2016-2017. In the second part were analyzed severe uncontrolled emissions of particulate matter (PM) and VOCs (April-May 2021) from the CPC, based in Capuava air quality station (AQS, CETESB) data and applying the Gaussian plume model AERMOD (steady-state plume model), estimating the concentrations of VOC and particulate matter (PM10). Finally, an analysis of benzene and toluene hourly data was provided from six air quality stations (Capuava, Paulínia, Cubatão, Pinheiros, São José dos Campos e São José-Vista Verde) of São Paulo state, from 2017 to 2022. The results of sampling (Tenax tubes) and analysis (GC-FID) showed that in the surroundings of the CPC, the most abundant compounds were toluene (1.5 ± 1.1 ppbv), cis-2-hexene (1.4 ± 1.9 ppbv), benzene (0.55 ± 0.66 ppbv) and m+p-xylene (0.58 ± 0.3 ppbv). The correlations and ratios among BTEX showed the influence from industrial sources despite vehicular emissions have been the main sources of these compounds around CPC. The estimation of the potential impacts associated to CPC emissions for the formation of secondary pollutants showed that aromatic compounds represented ~98 % and ~68% of the total SOA and O3 formation, respectively. The estimation of the lifetime cancer risk (LCR) due to benzene was six times higher than the EPA recommendation and could negatively affect the populations health in this region. The episode of uncontrolled emissions (April-May 2021) compared to the four previous years showed increase in the mean concentrations by a factor of 2 for PM10, benzene, and toluene, reaching maximum values during the episode: 174 µg m-3 (PM10), 22.8 ppb (benzene) and 14.3 ppb (toluene). AERMOD showed that the VOC plume had the potential to reach a large part of Mauá and Santo André municipalities, with the potential to affect the health of more than 1 million inhabitants. Finally, the CETESB AQS analyses for the period (2017-2022), benzene shows higher annual mean concentrations at the sites located in industrialized areas (Capuava 2017: 0.78 ppb; Cubatão 2018: 0.70 ppb; Capuava 2019: 0.78 ppb, 2020: 0.72 ppb, 2021: 1.15 ppb and 2022: 0.78 ppb), however, a less clear profile was observed for toluene, since the higher concentrations were observed for industrial or urban-traffic areas (Capuava 2017: 1.3 ppb; Pinheiros 2018: 1.7 ppb; 2019: 1.2 ppb; São José dos Campos 2020: 1.7 ppb; Capuava 2021: 1.4 ppb and Cubatão 2022: 1.5 ppb). Additionally diurnal profiles of toluene at industrial areas do not corresponds to typical traffic emissions. The estimation of LCR due to benzene was ranged from 1.0 x 10-6 to 1.0 x 10-5, reaching up ten times higher than the EPA recommendation. This observation provides an overview of the concentrations for the other industrial areas in São Paulo state. Results provided significantly important information on the effects of airborne emissions from the Capuava petrochemical and industrial complex on air quality in a densely urbanized area, analyzing data from an official AQS, modeled (AERMOD) and measurements results for an area with high potential of air contamination in Brazil.